Alumina carrier and its forming method and application in hydrogenation reaction
By adding foamed microspheres to the alumina dry adhesive powder and using extrusion molding technology, an alumina support with penetration bimodal pore structure and high mechanical strength was prepared, which solved the problem of macromolecular asphaltene diffusion in the residual oil hydrogenation reaction, and achieved efficient demetalization activity and long catalyst life.
Patent Information
- Application Number
- CN202210037505.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-13
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2042-01-13
AI Technical Summary
The existing macroporous alumina carrier cannot meet the demand for macromolecular asphaltene diffusion in residual oil hydrogenation reaction, and traditional pore reaming methods have problems such as decreased mechanical strength and poor pore penetration.
Alumina dry adhesive powder is used to mix with foamed microspheres, and the through-bian pore structure and high mechanical strength of the alumina support are achieved through extrusion strip forming and controlling temperature and pressure.
The prepared alumina support has a high proportion of micron-scale pores, which can effectively diffuse macromolecular asphaltene, and has high demetallic activity and long catalyst life for residual oil hydrogenation reactions.
Smart Images

Figure BDA0003468561890000101 
Figure BDA0003468561890000111
Abstract
Description
Technical Field
[0001] The invention relates to an alumina carrier and a molding method thereof and application thereof in hydrogenation reaction, and in particular to an alumina carrier suitable for a hydrogenation catalyst in the petrochemical industry and a molding method thereof and application thereof. Background Art
[0002] In the oil refining industry, heavy oil, especially residual oil, contains a large amount of metals, such as Fe, Ca, Ni, V, Na, etc., among which the metals are mainly enriched in asphaltene and colloid. With the increasing trend of heavy and inferior crude oil in the world, the difficulty of residual oil hydrogenation is also increasing. When processing inferior residual oil with a metal (Ni+V) mass fraction of about 200-300ppm and a residual carbon value of nearly 20%, it is necessary to develop a high-performance catalyst with high metal capacity and better diffusion performance. For such inferior residual oil, the diameter of its asphaltene molecules is further expanded, so the asphaltene molecules are subject to severe internal diffusion control, and are easily concentrated on the outer surface of the catalyst to react, resulting in severe pore blockage, which in turn causes a rapid increase in pressure drop and affects the normal operation of the device. Therefore, when processing ultra-high metal residual oil, the hydrogenation catalyst is required to have micron-level pores suitable for the diffusion of larger asphaltene molecules.
[0003] The existing macroporous alumina carrier cannot meet the requirements of directly generating micron-level pores, so it is a good choice to expand the existing alumina carrier to form a pore size distribution with bimodal pores of ten nanometers and micron-level pores. However, whether a physical pore expander or a chemical pore expander is used, the existing pore expansion means have problems such as low efficiency of the pore expander, the need for a higher proportion of pore expanders, poor penetration of super-large pores, and the formation of ink bottle-shaped pores, which leads to a decrease in the mechanical strength of the catalyst. For example, CN 102861615B discloses a method for preparing an alumina carrier, which uses pseudo-boehmite, an extrusion aid, a chemical pore expander, an ammonium salt, a physical pore expander carbon black powder, and water to mix and knead extruded strips, but the pores formed by thermal decomposition of the ammonium salt and the holes formed by ablation of carbon black have poor penetration and low mechanical strength, and the utilization efficiency of the pore expander is low. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides an alumina carrier and a molding method thereof and an application thereof in a hydrogenation reaction. The alumina carrier prepared by the molding method has a through bimodal pore structure adjustable within a certain range, has a high proportion of micron-level pores, can meet the diffusion requirements of macromolecular asphaltene, and has the characteristics of high demetallization activity and long catalyst life when applied to the hydrogenation reaction of super-heavy residue oil.
[0005] The first aspect of the present invention provides an alumina carrier, which has a through bimodal pore structure, and the pore volume of the alumina carrier is 0.9-1.4 mL / g; the pore volume occupied by pores with a pore diameter of 1-15 nm is 37%-94% of the total pore volume; the pore volume occupied by pores with a pore diameter of 5μm-20μm is 5%-62% of the total pore volume.
[0006] According to the present invention, preferably, in the alumina carrier, the pore volume of pores with a pore diameter of 1 to 15 nm accounts for 38% to 84% of the total pore volume; the pore volume of pores with a pore diameter of 5 μm to 20 μm accounts for 10% to 60% of the total pore volume.
[0007] According to the present invention, preferably, in the alumina carrier, the pore volume occupied by pores with a pore diameter of 1 to 15 nm is 38% to 84% of the total pore volume, preferably 74% to 84%; the pore volume occupied by pores with a pore diameter of 5 μm to 10 μm is 10% to 60% of the total pore volume, preferably 10% to 25%.
[0008] According to the present invention, preferably, in the alumina carrier, the pore volume occupied by pores with a pore diameter of 1 to 15 nm is 38% to 68%, preferably 38% to 48%, of the total pore volume; the pore volume occupied by pores with a pore diameter greater than 10 μm and less than or equal to 20 μm is 30% to 60%, preferably 50% to 60% of the total pore volume.
[0009] According to the present invention, preferably, in the alumina carrier, the pore volume of pores with a pore diameter of 1 to 15 nm is 38% to 84% of the total pore volume; within this range, the pore volume of pores with a pore diameter of 1 to 15 nm accounts for 38% to 84% of the total pore volume, and its non-limiting specific point values can be 38%, 40%, 45%, 48%, 53%, 58%, 63%, 68%, 74%, 77%, 80%, 82%, 84% and the like.
[0010] According to the present invention, preferably, the pore volume of the alumina carrier is 0.95 to 1.3 mL / g.
[0011] According to the present invention, the specific surface area of the alumina carrier is 80 to 300 m 2 / g, preferably 100 to 180 m 2 / g.
[0012] According to the present invention, the mechanical strength of the alumina carrier is 10 to 30 N / mm, preferably 10 to 20 N / mm.
[0013] According to the present invention, the shape of the alumina carrier can be a conventional shape in the art, such as a columnar, spherical, ellipsoidal, cylindrical, bar, impeller, toothed ball, clover, four-leaf clover and other special shapes, and holes can be opened on it, and grooves can be provided on the outer surface.
[0014] The second aspect of the present invention provides a method for forming the above-mentioned alumina carrier, comprising the following steps:
[0015] (1) Mix the aluminum oxide dry glue powder and the foamed microspheres evenly;
[0016] (2) kneading and shaping the materials after mixing in step (1);
[0017] (3) Drying and calcining the molded product obtained in step (2) to obtain an alumina carrier.
[0018] According to the present invention, the expanded microspheres in step (1) have a double-shell core-shell structure, wherein the intermediate shell is a thermoplastic acrylonitrile polymer, the inner core is a hydrocarbon, and the outermost shell is a calcium carbonate wrapping layer.
[0019] According to the present invention, the particle size of the expanded microspheres in step (1) is 20 μm to 40 μm, preferably 25 μm to 35 μm.
[0020] According to the present invention, the initial volatilization temperature of the hydrocarbon compound in the core of the foamed microsphere in step (1) is 1-50° C., preferably 25-40° C. The softening temperature of the intermediate shell layer is 50-120° C., preferably 50-90° C.
[0021] According to the present invention, the expanded microspheres in step (1) have a core volume of 50-90% of the total volume, a middle shell volume of 5-30% of the total volume, and a coating layer volume of 1-20% of the total volume, based on the total volume of the expanded microspheres.
[0022] According to the present invention, the average particle size of the expanded microspheres in step (1) is 20 μm to 40 μm.
[0023] According to the present invention, the expanded microspheres in step (1) can be commercial products or prepared according to existing technologies. The commercial products of the expanded microspheres can be EM series expanded microspheres EM-10 produced by POLYCHEM Company of the United States.
[0024] According to the present invention, the weight of the expanded microspheres added in step (1) is 2% to 30% of the weight of the alumina dry rubber powder, preferably 3% to 15%.
[0025] According to the present invention, water, preferably deionized water, needs to be added in step (1); the amount of water added is 70% to 160% of the weight of the aluminum oxide dry rubber powder, preferably 110% to 130%. Water is added together with other raw materials in step (1).
[0026] According to the present invention, an extrusion aid can be added in step (1), and the extrusion aid is one or more of sesbania powder, cellulose, polyvinyl alcohol, polyacrylamide, methyl cellulose, and hydroxypropyl methyl cellulose; the amount of the extrusion aid added is 1% to 5% by weight of the alumina dry rubber powder, preferably 2% to 4%. The extrusion aid is added together with other raw materials in step (1).
[0027] According to the present invention, a peptizing agent may be added in step (1), wherein the peptizing agent is one or more of nitric acid, citric acid, sulfuric acid, acetic acid, and hydrochloric acid, and the amount added is 1% to 5% by weight of the alumina dry glue powder, preferably 2% to 3%. The peptizing agent is added together with the other raw materials in step (1).
[0028] According to the present invention, the forming in step (2) is extrusion forming.
[0029] According to the present invention, preferably, the molding process in step (2) should be controlled at a temperature of 80-140° C., preferably 80-100° C. Preferably, the molding process should be controlled at a temperature higher than the softening temperature of the middle shell layer of the expanded microspheres.
[0030] According to the present invention, preferably, the pressure during the molding process in step (2) should be controlled to be 100 kg / cm 2 ~180kg / cm 2 .
[0031] According to the present invention, the drying in step (3) is performed at 50-150°C for 1h-5h; the calcination is performed at 500-1000°C for 2h-5h, preferably 800-1000°C.
[0032] According to the present invention, a third aspect of the present invention provides use of the above-mentioned alumina carrier or the alumina carrier prepared by the above-mentioned method in a residual oil hydrogenation reaction.
[0033] When used as a hydrogenation catalyst, the active metal component can be loaded by common means in the art. The active metal is a metal of Group VIB and / or Group VIII, the metal of Group VIB is preferably molybdenum and / or tungsten, and the metal of Group VIII is preferably cobalt and / or nickel. Based on the mass of the carrier, the content of Group VIB metal oxide is 1% to 20%, and the content of Group VIII metal oxide is 0.1% to 8%.
[0034] According to the present invention, the raw material for the hydrotreatment is low-quality residual oil, and the properties of the low-quality residual oil are as follows: the Ni+V content is 160-450 ppm. The content is mass content.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) In the present invention, the alumina carrier has a through bimodal pore structure, the alumina carrier has a through bimodal pore structure, the pore volume of the alumina carrier is 0.9-1.4 mL / g; the pore volume of pores with a pore diameter of 1-15 nm accounts for 37%-94% of the total pore volume; the pore volume of pores with a pore diameter of 5 μm-20 μm accounts for 5%-62% of the total pore volume. The alumina carrier of the present invention has a through bimodal pore structure that is adjustable within a certain range, has a high proportion of micron-sized pores, and can be used for residual oil hydrogenation reaction, especially can meet the diffusion requirements of macromolecular asphaltene in inferior residual oil with a Ni+V content of 160-450 ppm, and is used in residual oil hydrogenation reaction, and has the characteristics of easy diffusion of macromolecular asphaltene and high demetallization activity.
[0037] (2) In the present invention, in the molding method of the alumina carrier, a small amount of foamed microspheres are added to the alumina dry rubber powder, and the foamed microspheres are moderately and controllably expanded by controlling the appropriate temperature during extrusion molding, through the shape limitation of the extruder and the extrusion pressure, thereby obtaining an alumina carrier having an adjustable through-bimodal pore distribution and high mechanical strength. The method of the present invention avoids the problems of using a traditional pore expander to expand the pores to obtain micron-sized pores, such as a large amount of pore expander, poor mechanical strength, poor penetration of super-large pores, and the formation of ink bottle-shaped pores. The alumina expanded with foamed microspheres is particularly suitable for use as a heavy oil hydrogenation catalyst carrier. The hydrogenation catalyst obtained by loading the active metal on the alumina carrier has the characteristics of high demetallization activity and long catalyst life when used in the residual oil hydrogenation reaction.
[0038] (3) In the present invention, the alumina carrier is suitable for use as a residue oil hydrogenation catalyst carrier. The hydrogenation catalyst obtained by loading the active metal component on the alumina carrier has the characteristics of high demetallization activity and long catalyst life in the hydrogenation reaction of super-heavy low-quality residue oil. DETAILED DESCRIPTION
[0039] The effects and results of the method of the present invention are further described below with reference to the embodiments, but are not limited to the following embodiments.
[0040] In the present invention, the pore volume and pore distribution are measured by mercury intrusion method; the mechanical strength is measured by a particle strength tester; and the specific surface area is measured by BET method.
[0041] The alumina dry glue powder used in the examples and comparative examples of the present invention is macroporous aluminum hydroxide, and its specific surface area is 245m 2 / g, pore volume is 0.89mL / g, and pore diameter is 12.5nm; pore distribution: pore diameters of 1-15nm account for 96.7%, and 16nm-900nm account for 3.3%.
[0042] In each example of the present invention, based on the total volume of the expanded microspheres, the volume of the inner core accounts for 70% of the total volume, the volume of the intermediate shell layer accounts for 20% of the total volume, and the volume of the coating layer accounts for 10% of the total volume.
[0043] In the present invention, the properties of the batch of EM-10 products in Examples 1 and 3 are: average particle size of 30 μm, initial volatilization temperature of the core hydrocarbons of 30° C., and softening temperature of the thermoplastic acrylate polymer in the intermediate shell layer of 80° C. The properties of EM-10 in Comparative Examples 1 to 3 are the same as those in Example 1.
[0044] In the present invention, the properties of the batch of EM-10 products in Examples 2 and 4 are as follows: the average particle size is 35 μm, the initial volatilization temperature of the core hydrocarbon is 25° C., and the softening temperature of the thermoplastic acrylate polymer in the intermediate shell is 60° C.
[0045] In the present invention, the Ni removal rate / % and V removal rate / % of the embodiments and comparative examples are:
[0046] Ni removal rate / %=1-(Ni mass content in produced oil / Ni mass content in raw oil)×100%;
[0047] V removal rate / %=1-(V mass content in the produced oil / V mass content in the raw oil)×100%.
[0048] Example 1
[0049] Weigh 3g of EM-10 microspheres, mix the microspheres with 100g of alumina dry powder and 120g of deionized water, and knead them thoroughly. Put the kneaded materials into an extruder that can measure the temperature and cool the materials for extrusion molding. The molding process temperature is controlled at 90°C and the extrusion pressure is 140kg / cm 2 The alumina wet strips were obtained after pore expansion. The strips were dried at 90°C in an oven at normal pressure for 2 hours, and then calcined at 850°C for 3 hours to obtain the alumina carrier.
[0050] The pore volume of the prepared alumina carrier is 0.99mL / g, the pore volume occupied by pores with a pore diameter of 1 to 15nm accounts for 80.9% of the total pore volume, the pores with a pore diameter greater than 15nm are mainly distributed in 10μm to 15μm (excluding 10μm), and the pore volume occupied by 10μm to 15μm (excluding 10μm) accounts for 15.1% of the total pore volume. The mechanical strength of the alumina carrier is 15N / mm, and the specific surface area is 120m 2 / g.
[0051] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0052] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties of the residual oil hydrogenation reaction are shown in Table 1. The hydrogenation reaction conditions are: temperature 380°C, pressure 15MPa, liquid hourly volume space velocity 1h -1 , hydrogen to oil volume ratio 760. The hydrogenation effect is shown in Table 2.
[0053] Example 2
[0054] Weigh 15g of EM-10 microspheres, mix the microspheres with 100g of alumina dry rubber powder and 120g of deionized water, and knead them thoroughly. Put the kneaded materials into an extruder that can measure the temperature and cool the materials for extrusion molding. The molding process temperature is controlled at 80°C and the extrusion pressure is 140kg / cm 2 The alumina wet strips were obtained after pore expansion. The strips were dried at 80°C in an oven for 2 hours at normal pressure, and then calcined at 850°C for 3 hours to obtain the alumina carrier.
[0055] The pore volume of the prepared alumina carrier is 1.28mL / g, the pore volume of pores with a pore diameter of 1 to 15nm accounts for 40.1% of the total pore volume, the pores with a pore diameter greater than 15nm are mainly distributed in 10μm to 15μm (excluding 10μm), and the pore volume of pores of 10μm to 15μm (excluding 10μm) accounts for 59.1% of the total pore volume. The mechanical strength of the carrier is 10N / mm, and the specific surface area is 100m 2 / g.
[0056] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% tungsten oxide and 2wt% cobalt oxide based on the mass of the carrier.
[0057] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0058] Example 3
[0059] Weigh 3g of EM-10 microspheres, mix the microspheres with 100g of alumina dry powder and 120g of deionized water, and knead them thoroughly. Put the kneaded materials into an extruder that can measure the temperature and cool the materials for extrusion molding. The molding process temperature is controlled at 90°C and the extrusion pressure is 100kg / cm 2 The alumina wet strip after pore expansion was obtained, dried at 90°C in an oven at normal pressure for 2 hours, and then calcined at 850°C for 3 hours to obtain an alumina carrier.
[0060] The pore volume of the prepared alumina carrier is 1.1mL / g, and the pore volume of pores with a pore diameter of 1 to 15nm accounts for 80.6% of the total pore volume. The pores with a pore diameter greater than 15nm are mainly distributed in 15μm to 20μm (excluding 15μm), and the pore volume of pores of 15μm to 20μm (excluding 15μm) accounts for 16.9% of the total pore volume. The mechanical strength of the carrier is 13N / mm, and the specific surface area is 125m 2 / g.
[0061] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% tungsten oxide and 2wt% nickel oxide based on the mass of the carrier.
[0062] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0063] Example 4
[0064] Weigh 3g of EM-10 microspheres, mix the microspheres with 100g of alumina dry powder and 120g of deionized water, and knead them thoroughly. Put the kneaded materials into an extruder that can measure the temperature and cool the materials for extrusion molding. The molding process temperature is controlled at 90°C and the extrusion pressure is 180kg / cm 2 The alumina wet strip after pore expansion was obtained, dried at 90°C in an oven at normal pressure for 2 hours, and then calcined at 850°C for 3 hours to obtain an alumina carrier.
[0065] The pore volume of the alumina carrier is 0.97 mL / g, and the pore volume of pores with a pore diameter of 1 to 15 nm accounts for 83.1% of the total pore volume. The pores with a pore diameter greater than 15 nm are mainly distributed in the range of 5 μm to 10 μm, and the pore volume of 5 μm to 10 μm accounts for 14.5% of the total pore volume. The mechanical strength of the carrier is 17 N / mm, and the specific surface area is 125 m 2 / g.
[0066] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% of molybdenum oxide and 2wt% of cobalt oxide based on the mass of the carrier.
[0067] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0068] Comparative Example 1
[0069] Weigh 3g of EM-10 microspheres, mix the microspheres with 100g of alumina dry rubber powder and 120g of deionized water, and knead them thoroughly. Put the kneaded materials into an extruder that can measure the temperature and cool the materials for extrusion molding. The molding process temperature is controlled at 50°C and the extrusion pressure is 140kg / cm 2 The alumina wet strips were obtained after pore expansion. The strips were dried at 90°C in an oven at normal pressure for 2 hours, and then calcined at 850°C for 3 hours to obtain the alumina carrier.
[0070] The pore volume of the alumina carrier is 0.93 mL / g, pores with a pore diameter of 1 to 15 nm account for 92.1%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 20 μm to 30 μm (excluding 20 μm), and the pore volume of 20 μm to 30 μm (excluding 20 μm) accounts for 3.8% of the total pore volume. The mechanical strength of the carrier is 20 N / mm, and the specific surface area is 127 m 2 / g.
[0071] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0072] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0073] Comparative Example 2
[0074] Weigh 3g of EM-10 microspheres, mix the microspheres with 100g of alumina dry rubber powder and 120g of deionized water, and knead them thoroughly. Put the kneaded materials into an extruder that can measure the temperature and cool the materials for extrusion molding. The molding process temperature is controlled at 200℃ and the extrusion pressure is 140kg / cm 2 The alumina wet strips were obtained after pore expansion. The strips were dried at 90°C in an oven at normal pressure for 2 hours, and then calcined at 850°C for 3 hours to obtain the alumina carrier.
[0075] The pore volume of the alumina carrier is 0.91 mL / g, pores with a pore diameter of 1 to 15 nm account for 92.5%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 20 μm to 30 μm (excluding 20 μm), and the pore volume of 20 μm to 30 μm (excluding 20 μm) accounts for 3.6% of the total pore volume. The mechanical strength of the carrier is 20 N / mm, and the specific surface area is 128 m 2 / g.
[0076] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0077] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0078] Comparative Example 3
[0079] Weigh 3g of EM-10 microspheres, mix the microspheres with 100g of alumina dry rubber powder and 120g of deionized water, and knead them thoroughly. Put the kneaded materials into an extruder that can measure the temperature and cool the materials for extrusion molding. The molding process temperature is controlled at 150℃ and the extrusion pressure is 140kg / cm 2 The alumina wet strips were obtained after pore expansion. The strips were dried at 90°C in an oven at normal pressure for 2 hours, and then calcined at 850°C for 3 hours to obtain the alumina carrier.
[0080] The alumina carrier obtained by extrusion has a bursting phenomenon and irregular shape. The pore volume of the obtained alumina carrier is 1.1mL / g, and the pore volume occupied by pores with a pore diameter of 1 to 15nm accounts for 75.9% of the total pore volume. The pores with a pore diameter greater than 15nm are mainly distributed in 30μm to 40μm (excluding 30μm), and the pore volume occupied by 30μm to 40μm (excluding 30μm) accounts for 19.1% of the total pore volume. The mechanical strength of the alumina carrier is 8N / mm, and the specific surface area is 98m 2 / g.
[0081] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0082] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0083] Comparative Example 4
[0084] Weigh 3g of acrylonitrile-methacrylonitrile copolymer, 100g of alumina dry rubber powder and 120g of deionized water, mix and knead thoroughly, and put the kneaded materials into a high-temperature resistant extruder capable of material temperature measurement, cooling and heating for extrusion molding. The molding process temperature is controlled at 90°C and the extrusion pressure is 140kg / cm 2 The alumina wet strips were obtained after pore expansion. The strips were dried at 90°C in an oven at normal pressure for 2 hours, and then calcined at 850°C for 3 hours to obtain the alumina carrier.
[0085] The pore volume of the alumina carrier is 0.90 mL / g, pores with a pore diameter of 1 to 15 nm account for 96.1%, pores with a pore diameter greater than 15 nm are mainly distributed in the range of 16 nm to 25 nm, and the pore volume of pores with a diameter of 16 nm to 25 nm accounts for 2.1% of the total pore volume. The mechanical strength of the alumina carrier is 24 N / mm. The specific surface area is 131 m 2 / g.
[0086] The alumina carrier is impregnated with an impregnation liquid containing active metals to obtain a hydrogenation catalyst. The hydrogenation catalyst contains 5wt% molybdenum oxide and 2wt% nickel oxide based on the mass of the carrier.
[0087] The above hydrogenation catalyst was applied to the residual oil hydrogenation reaction. The raw oil properties and hydrogenation reaction conditions of the residual oil hydrogenation reaction were the same as those in Example 1. The hydrogenation effect is shown in Table 2.
[0088] Table 1 Raw oil properties
[0089] nature Raw oil-Maya residue <![CDATA[Density (20 °C) / g·cm -3 > 0.997 Ni / ppm 65 V / ppm 335
[0090] Table 2 Hydrogenation effect of the catalyst obtained in each example
[0091]
[0092]
[0093] The above describes the specific implementation of the present invention in detail, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the various technical features being combined in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. Application of an alumina carrier in residual oil hydrogenation reaction; The alumina carrier has a through bimodal pore structure, wherein the pore volume of the alumina carrier is 0.9-1.4 mL / g; the pore volume occupied by pores with a pore diameter of 1-15 nm accounts for 37%-94% of the total pore volume; the pore volume occupied by pores with a pore diameter of 5 μm-20 μm accounts for 5%-62% of the total pore volume; The molding method of the alumina carrier comprises the following steps: (1) Mix the alumina dry glue powder and the foamed microspheres evenly; (2) kneading and molding the mixed materials in step (1); (3) drying and calcining the molded product obtained in step (2) to obtain an alumina carrier; The expanded microspheres in step (1) have a double-shell core-shell structure, wherein the middle shell is a thermoplastic acrylonitrile polymer, the inner core is a gaseous hydrocarbon, and the outermost shell is a calcium carbonate wrapping layer; The expanded microspheres described in step (1) are characterized in that, based on the total volume of the expanded microspheres, the volume of the inner core accounts for 50-90% of the total volume, the volume of the intermediate shell layer accounts for 5-30% of the total volume, and the volume of the wrapping layer accounts for 1-20% of the total volume; The weight of the expanded microspheres added in step (1) is 2% to 30% of the weight of the alumina dry rubber powder; The molding process should be controlled at a temperature of 80-140°C.
2. The application according to claim 1, characterized in that: In the alumina carrier, the pore volume of pores with a pore diameter of 1-15 nm accounts for 38%-84% of the total pore volume; the pore volume of pores with a pore diameter of 5 μm-10 μm accounts for 10%-60% of the total pore volume.
3. The application according to claim 2, characterized in that: In the alumina carrier, the pore volume of pores with a pore diameter of 1-15 nm accounts for 74%-84% of the total pore volume; the pore volume of pores with a pore diameter of 5 μm-10 μm accounts for 10%-25% of the total pore volume.
4. The use according to claim 1, characterized in that: In the alumina carrier, the pore volume of pores with a diameter of 1-15 nm accounts for 38%-68% of the total pore volume; the pore volume of pores with a diameter of greater than 10 μm and less than or equal to 20 μm accounts for 30%-60% of the total pore volume.
5. The application according to claim 4, characterized in that: In the alumina carrier, the pore volume of pores with a diameter of 1-15 nm accounts for 38%-48% of the total pore volume; the pore volume of pores with a diameter of greater than 10 μm and less than or equal to 20 μm accounts for 50%-60% of the total pore volume.
6. The use according to claim 1, characterized in that: The softening temperature of the middle shell layer of the foamed microspheres in step (1) is 50-120°C; the initial volatilization temperature of the hydrocarbon in the inner core is 1-50°C.
7. The use according to claim 6, characterized in that: The softening temperature of the middle shell layer of the foamed microspheres in step (1) is 50-90°C; the initial volatilization temperature of the hydrocarbon in the inner core is 25-40°C.
8. The use according to claim 1 or 6, characterized in that: The average particle size of the expanded microspheres in step (1) is 20 μm to 40 μm.
9. The use according to claim 1, characterized in that: The weight of the expanded microspheres added in step (1) is 3% to 15% of the weight of the alumina dry rubber powder.
10. The use according to claim 1, characterized in that: The molding process in step (2) should be controlled at a pressure of 100 kg / cm 2 ~180kg / cm 2 .
11. The use according to claim 1, characterized in that: The molding in step (2) is extrusion molding; the temperature of the molding process should be controlled at 80-100°C.
12. The use according to claim 6 or 11, characterized in that: The molding process should be carried out at a temperature higher than the softening temperature of the middle shell layer of the expanded microspheres.
Citation Information
Patent Citations
Preparation method of macroporous alumina carrier
CN102861615B
Process for preparation of a catalyst carrier
CN101237927A
Alumina carrier with composite pore structure and preparation method thereof
CN102614934A